Methylation of Promoter Regions of Genes of the Human Intrauterine Renin Angiotensin System and Their Expression. (30th March 2015) - Sykes, Shane D.; Mitchell, Carolyn; Pringle, Kirsty G.; Wang, Yu; Zakar, Tamas; Lumbers, Eugenie R.
Abstract : The intrauterine renin angiotensin system (RAS) is implicated in placentation and labour onset. Here we investigate whether promoter methylation of RAS genes changes with gestation or labour and if it affects gene expression. Early gestation amnion and placenta were studied, as were term amnion, decidua, and placenta collected before labour (at elective caesarean section) or after spontaneous labour and delivery. The expression and degree of methylation of the prorenin receptor ( ATP6AP2 ), angiotensin converting enzyme ( ACE ), angiotensin II type 1 receptor ( AGTR1 ), and two proteases that can activate prorenin (kallikrein, KLK1, and cathepsin D, CTSD ) were measured by qPCR and a DNA methylation array. There was no effect of gestation or labour on the methylation of RAS genes and CTSD . Amnion and decidua displayed strong correlations between the percent hypermethylation of RAS genes and CTSD, suggestive of global methylation. There were no correlations between the degree of methylation and mRNA abundance of any genes studied. KLK1 was the most methylated gene and the proportion of hypermethylated KLK1 alleles was lower in placenta than decidua. The presence of intermediate methylated alleles of KLK1 in early gestation placenta and in amnion after labour suggests that KLK1 methylation is uniquely dynamic in these tissues.